A Single-Center Radiographic Study on Temporomandibular Joint Condylar Morphology in Eastern Nepal - Regmee, Pragya; Luitel, Abhinaya; Maharjan, Iccha Kumar (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: The temporomandibular joint (TMJ) is a complex synovial joint critical for mastication, speech, and facial expression. Morphological variations of the mandibular condyle can influence joint function and susceptibility to disorders. Methods: A cross-sectional study was conducted at the Department of Oral Medicine and Radiology, B.P. Koirala Institute of Health Sciences, Dharan, Nepal. A total of 441 panoramic radiographs of patients aged ≥18 years were analyzed. Condylar morphology was evaluated and recorded. Data were analyzed using Microsoft Excel 2023, and frequency distributions were calculated. Results: The mean age was 40.31 years (177 males, 264 females). Round/oval condyles were the most common morphology (right: 297(67.3%); left: 295(66.9%)). Other variants included mixed (right: 54(12.2%); left: 32(7.3%)), bifid (right: 38(8.6%); left: 45(10.2%)), flat (right: 21(4.8%); left: 37(8.4%)), diamond (right: 22(5%); left: 23(5.2%)), crooked finger (right: 7(1.6%); left: 8(1.8%)), bulbous (1(0.2%) both sides), and condyle-in-condyle (1(0.2%) right side). Minor asymmetries were noted between sides. Conclusion: Round/oval condyles predominate in this Nepalese population, while rare variants and asymmetries exist. Awareness of these variations is crucial for accurate diagnosis, treatment planning, and management of TMJ disorders.